2004
DOI: 10.1098/rspb.2004.2699
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic monitoring on a humpback whale ( Megaptera novaeangliae ) feeding ground shows continual singing into late spring

Abstract: Singing by males is a major feature of the mating system of humpback whales, Megaptera novaeangliae (Borowski). Although a few songs have been opportunistically recorded on the whales' high-latitude feeding grounds, singing in these regions was thought to be only sporadic. We report results from the first continuous acoustic monitoring of a humpback whale feeding ground (off Cape Cod, MA, USA) in spring. Using autonomous sea-floor recording systems, we found singing on a daily basis over the entire 25 day moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(156 citation statements)
references
References 29 publications
8
147
0
1
Order By: Relevance
“…The song phrases shown in Figures 2 and 3 here for humpbacks located at NEGB and FB-GSC respectively are similar to one or more phrases of humpback songs recorded previously in the Gulf of Maine and other ocean regions [5,7,8,19,21,55,56]. The song call rate of between 11 to 35 calls per minute obtained here is consistent with the call rates for humpback songs shown in spectrograms of Refs.…”
Section: Discussionsupporting
confidence: 88%
“…The song phrases shown in Figures 2 and 3 here for humpbacks located at NEGB and FB-GSC respectively are similar to one or more phrases of humpback songs recorded previously in the Gulf of Maine and other ocean regions [5,7,8,19,21,55,56]. The song call rate of between 11 to 35 calls per minute obtained here is consistent with the call rates for humpback songs shown in spectrograms of Refs.…”
Section: Discussionsupporting
confidence: 88%
“…Although song is mainly concentrated during the mating season, and believed to be produced only by males, some singing is occasionally heard during migration, or at the summer feeding grounds (Clark & Clapham, 2004). Although songlike underwater sounds had been known by oceanographers for many years (and indeed, it has been suggested that singing Mediterranean humpbacks are the origin of the Greek myth of sirens singing) these vocalizations were not definitively linked to whales until the 1960s (Payne & McVay, 1971).…”
Section: Whale Songmentioning
confidence: 99%
“…Humpback whale song has been documented in many breeding areas (Payne et al 1983, Payne and Payne 1985, Cerchio et al 2001, Darling and Sousa-Lima 2005, Eriksen et al 2005, Murray et al 2012, Oviedo et al 2008. Additionally, song has been recorded during migration (Norris et al 1999, Noad et al 2000 and on a few feeding grounds (Clark and Clapham 2004, Stimpert et al 2012, Garland et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Many similarities have even been noted between distinct populations (Winn et al 1981, Cerchio et al 2001, Darling and Sousa-Lima 2005, Garland et al 2013). Due to the nature of migration, these distinct populations are able to transmit song across large distances (Noad et al 2000, Clark and Clapham 2004, Darling and Sousa-Lima 2005. Cultural transmission is thought to be one of the possible explanations for these large-scale changes and similarities within and between populations (Guinee et al 1983, Payne et al 1983, Garland et al 2011).…”
Section: Introductionmentioning
confidence: 99%